Soft Computing and Optimization Techniques for Sustainable Agriculture - Mishra, Debesh (Smart Computing Applications, 2022)
This book covers the emerging applications of different computational and optimization techniques in order to achieve a sustainable agriculture. A sustainable agricultural management requires tools in providing integrated, area-specifi c, and interpreted prediction or forecasting and guidance in every aspect in agriculture